Aortopathy – A surgical pathology experience - Pradeep Vaideeswar; Sujit Udayaravi (Indian Journal of Pathology and Microbiology)
Background: Aortopathy is a non-inflammatory and non-atherosclerotic disease of aorta that results from significant ‘degenerative’ changes in the media. This often leads to thoracic aortic aneurysms and/or dissections in young individuals. Aims: This study aimed to analyze the clinical and pathological features of aortic resections performed for aortopathy. Materials and Methods: Over the span of 15 years (2008-2022), all surgically resected specimens of aorta showing aortopathy in all age groups were studied. Particular attention was paid to the changes in the media to assess the extent, grade and severity of aortopathy. Results: During the 15-year study period, 73 surgically resected specimens of the ascending aorta showed features of aortopathy. There were 48 males and 25 females, who had chief complaints of dyspnea, chest pain and palpitation. The aortopathic manifestations observed were ascending aortic aneurysms (36 patients, 49.3%), aortic dissections (21 patients, 28.8%) and aneurysms with dissections (16 patients, 21.9%). Bicuspid aortic valve (24 cases), Marfan syndrome (13 cases) and hypertension (12 cases) were commonly identified. There was one case each of Loeys-Dietz syndrome, and aortopathy possibly related to blunt chest trauma. In a significant proportion of patients (22 cases), the cause remained elusive. Moderate to severe aortopathy was observed in 60 cases (82.2%). Conclusion: This study helps in standardizing the histological parameters of aortopathy. In patients where the cause is uncertain despite of detailed clinico-radiological assessment, there is a need for molecular and genetic studies.